POTENSI MAKANAN NASI TUMPANG LETHOK SEBAGAI DAYA TARIK WISATA DI DAERAH KLATEN - ESA MUTIARANI ESA MUTIARANI (Jurnal Budaya Nusantara, 2022)
The development of tourism can provide opportunities for the development of tourism products, namely culinary in the Klaten area. The high development of tourism provides a very large opportunity for the community, to participate in the development of culinary tourism, which is still very limited at this time. This paper aims to explain traditional food as a local culinary with the name Nasi Tumpang Lethok as a tourist attraction for the Klaten Region. The research method used is descriptive qualitative, using the theory of (Danamik & Weber, 2006) which explains that tourist attraction can be built through uniqueness, originality, authenticity, and diversity. Data was collected by observation and interviews. The results of this paper explain that the traditional local culinary food, Nasi Tumpang Lethok, is a type of traditional food that has a tourist attraction. The tourist attraction of the traditional food of Nasi Tumpang Lethok is because this traditional food has uniqueness, originality, authenticity, and diversity. The uniqueness can be seen from the combination of scarcity and uniqueness inherent in the traditional food of Nasi Tumpang Lethok. The originality of traditional food is reflected in the authenticity of traditional food ingredients while maintaining the original local raw materials and processes by describing their authenticity, diversity leads to variations in shapes and name